2023
DOI: 10.1007/s40120-022-00435-8
|View full text |Cite|
|
Sign up to set email alerts
|

Off-time Treatment Options for Parkinson’s Disease

Abstract: Motor fluctuations (MF) are deemed by patients with Parkinson's disease (PD) as the most troublesome disease feature resulting from the increasing impairment in responsiveness to dopaminergic drug treatments. MF are characterized by the loss of a stable response to levodopa over the nychthemeron with the reappearance of motor (and non-motor) parkinsonian clinical signs at various moments during the day and night. They normally appear after a few years of levodopa treatment and with a variable, though overall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 151 publications
0
10
0
2
Order By: Relevance
“…Despite considerable research, to date, no disease-modifying therapy for PD has been identified, 2 so treatment remains symptomatic, the primary aim being to replace lost dopamine, restore motor control, and minimize the time patients spend in the off state. 3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite considerable research, to date, no disease-modifying therapy for PD has been identified, 2 so treatment remains symptomatic, the primary aim being to replace lost dopamine, restore motor control, and minimize the time patients spend in the off state. 3…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite considerable research, to date, no diseasemodifying therapy for PD has been identified, 2 so treatment remains symptomatic, the primary aim being to replace lost dopamine, restore motor control, and minimize the time patients spend in the off state. 3 Initial treatment of PD is generally with the "goldstandard" oral therapy, levodopa, which is converted to dopamine in the brain. However, commonly after a few years of treatment, levodopa becomes less effective in controlling symptoms, resulting in motor fluctuations (eg, end-of-dose wearing off, delayed on) and dyskinesias (involuntary movements).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, based on the analysis of kinetic inhibition, pH-dependence, and L-carnitine sensitivity, the amantadine transport system is likely to be different from other putative cation transport systems of the inner BRB, which transport verapamil, clonidine, and propranolol [ 3 , 4 , 5 ]. Adamantane derivatives, such as amantadine and memantine, are known to exert neuroprotective effects by inhibiting N-methyl-D-aspartate (NMDA) receptors [ 6 , 7 , 8 , 9 ] and are used for the treatment of neurodegenerative disorders of the brain [ 10 , 11 , 12 , 13 ]. Previous studies showed that the overactivation of NMDA receptors caused damage to retinal ganglion cells [ 14 , 15 , 16 ] and it is considered a mechanism of retinal neurodegeneration under pathological conditions, such as glaucoma [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The term DAT refers to deep brain stimulation (DBS), subcutaneous infusion of apomorphine and continuous infusion of levodopa/carbidopa intestinal gel with or without entacapone. 2 However, timely referral for DAT remains challenging. Not all eligible patients are referred to a specialized center in time, while others may be referred too early, both attributable to a lack of clear and objective referral criteria.…”
mentioning
confidence: 99%